Remittances in Pakistan: Why They Have Gone Up and Why They Are Not Coming Down (The Pakistan Development Review, 2011)
The flow of workers’ remittances to Pakistan has more than quadrupled in the last eight years and shows no sign of slowing down, despite the economic downturn in the Gulf Cooperation Council and other important host countries for Pakistani workers. This paper analyses the forces that have driven remittance flows to Pakistan in recent years. A methodological innovation is that we study the behaviour of per capita remittances and draw a close link between remittances and remitters’ earning capacity, in the belief that higher earning power leads to more remittances. Our main conclusions are that (i) the growth in the inflow of workers’ remittances to Pakistan is in large part due to an increase in worker migration, (ii) the higher skill levels of migrating workers has helped boost remittances, and (iii) other imporant determinants of remittances to Pakistan are agricultural output and the relative yield on investments in the host and home countries. JEL classification: F22, F24 Keywords: Workers’ Remittances, Migration, Pakistan